The Influence of Cyber Public Relations Strategy on Consumer Trust of QRIS Users - Melviana, Yunika; Ghanistyana, Lathifa Prima; Wahyuni, Anjelina Intan; Susanti, Dina; Utami, Ananda Halisya (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This research study aims to quantify the extent of impact of Cyber Public Relations strategies to the level of trust towards QRIS by digital consumers. QRIS (Quick Response Code Indonesian Standard) is a digital payment system whose payment technology is based on QR-code that users can scan via the mobile phone. QRIS is gaining momentum in the fast-growing digital environment since it is convenient, effective, and aligned with the cashless-society project in Indonesia. Cyber Public Relations strategies are online communication programs undertaken by an institution or company to develop an organizational image, consumer involvement, as well as create faith in their services. The current research is a quantitative study of Cyber PR strategy and the extent of confidence with QRIS that uses the survey research design and the population of 100 respondents who use digital services. The results reveal that Cyber Public Relations actions have a powerful impact on the trust of QRIS users. As a result, it can be thus concluded that successful use of digital communications through Cyber PR practices is invaluable in making good impressions and in establishing consumer beliefs in QRIS as a secure and reliable mode of digital payment.